The Work-family Field: Gaps and Missing Links as Opportunities for Future Research (2017)
This review presents a synthesis and a critique of the development of the existing workfamily (WF) literature during the last decade in order to highlight gaps and limitations in current research. The study revises 83 peer-reviewed articles, book chapters and conference presentations (2004-2014) related to WF in economics, management and psychology disciplines, and classifies the current research into three broad themes for future research paths: i) definitions and theories; ii) background and outcomes of wf conflict, balance and enrichment; and iii) methodological gaps. Advances have been made this decade on meta-analysis and the understanding of the positive side of WF interface. Future research opportunities in this field will include a deeper understanding of how to effectively cope with WF conflict, how to achieve WF enrichment, the use of different methods (qualitative, longitudinal and experimental studies) on samples of new occupations, and how researchers could address methodological problems (causality, endogeneity, simultaneity, effect size, and self-selection bias) to better handle the complexity of WF issues.